Design of Broadband and Wide-Angle Hexagonal Metamaterial Absorber Based on Optimal Tiling of Rhombus Carbon Pixels and Implantation of Copper Cylinders - Yongjune Kim (MDPI AG, 2021)
A design method for a broadband and wide-angle metamaterial absorber is proposed based on optimal tiling of rhombus carbon pixels on and implantation of metal cylinders inside an acrylic substrate for which the backside is blocked by the perfect conductor. First, an intermediate carbon metapattern is achieved via optimal tiling of rhombus carbon pixels based on the genetic algorithm (GA), which can minimize the reflectances of both of the transverse electric (TE) and transverse magnetic (TM) polarized electromagnetic (EM) waves for the incident angles <semantics>0∘</semantics> and <semantics>60∘</semantics> simultaneously. Then, copper cylinders are implanted inside the substrate to boost the absorptions of both of the TE and TM polarizations for the <semantics>60∘</semantics> oblique incidences. To extend the absorption bandwidth, the design is finalized by evolving the intermediate metapattern using the GA. Based on the finalized carbon metapattern, the <semantics>90%</semantics> absorption bandwidth is confirmed in the frequency range 8.8 to 11.6 GHz, for which the fractional bandwidth is <semantics>27.5%</semantics> for both of the two polarizations with the incident angles from <semantics>0∘</semantics> to <semantics>60∘</semantics>. The proposed method could open a way to design a broadband and wide-angle EM metamaterial absorber that can be applied to the edges of three-dimensional structures such as a regular tetrahedron or square pyramid that have interior angles of <semantics>60∘</semantics> that cannot be covered by conventional square or rectangular metamaterial absorbers.